Global Monitoring Report, 2005 : Millennium Development Goals; From Consensus to Momentum. (World Economic and Financial Surveys; World Economic and Financial Surveys, 2005)
The year 2005 marks an important juncture for development as the international community takes stock of implementation of the Millennium Declaration-signed by 189 countries in 2000-and discusses how progress toward the Millennium Development Goals (MDGs) can be accelerated. The MDGs set clear targets for reducing poverty and other human deprivations and for promoting sustainable development. What progress has been made toward these goals, and what should be done to accelerate it? What are the responsibilities of developing countries, developed countries, and international financial institutions? Global Monitoring Report 2005 addresses these questions. This report, the second in an annual series assessing progress on the MDGs and related development outcomes, has a special focus on Sub-Saharan Africa-the region that is farthest from the development goals and faces the toughest challenges in accelerating progress. The report finds that without rapid action to accelerate progress, the MDGs will be seriously jeopardized-especially in Sub-Saharan Africa, which is falling short on all the goals. It calls on the international community to seize the opportunities presented by the increased global attention to development to build momentum for the MDGs. The report presents in-depth analysis of the agenda and priorities for action. It discusses improvements in policies and governance that developing countries need to make to achieve stronger economic growth and scale up human development and relevant key services. It examines actions that developed countries need to take to provide more and better development aid and to reform their trade policies to improve market access for developing country exports. And it evaluates how international financial institutions can strengthen and sharpen their support for this agenda. Global Monitoring Report 2005 is essential reading for development practitioners and those interested in international affairs.